2017
DOI: 10.1111/ppl.12549
|View full text |Cite
|
Sign up to set email alerts
|

AtbHLH68 transcription factor contributes to the regulation of ABA homeostasis and drought stress tolerance in Arabidopsis thaliana

Abstract: Basic helix-loop-helix (bHLH) transcription factors are involved in a wide range of developmental processes and in response to biotic and abiotic stresses. They represent one of the biggest families of transcription factors but only few of them have been functionally characterized. Here we report the characterization of AtbHLH68 and show that, although the knock out mutant did not have an obvious development phenotype, it was slightly more sensitive to drought stress than the Col-0, and AtbHLH68 overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…Subgroup IX bHLHs were proposed to be involved in photoperiodism flowering (FBH1-FBH4) [ 183 ] and facilitate stomatal opening through phosphorylation (AKS2) [ 184 ]. Two studied X proteins (bHLH068 and bHLH112) could response to abiotic stresses [ 185 , 186 ]. Subgroup XI members in Arabidopsis (LRL1-LRL5) [ 130 , 187 , 188 ] and rice (OsRHL1) [ 189 ] regulate root hair development, while another protein OsPTF1 is involved in phosphate starvation tolerance [ 190 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup IX bHLHs were proposed to be involved in photoperiodism flowering (FBH1-FBH4) [ 183 ] and facilitate stomatal opening through phosphorylation (AKS2) [ 184 ]. Two studied X proteins (bHLH068 and bHLH112) could response to abiotic stresses [ 185 , 186 ]. Subgroup XI members in Arabidopsis (LRL1-LRL5) [ 130 , 187 , 188 ] and rice (OsRHL1) [ 189 ] regulate root hair development, while another protein OsPTF1 is involved in phosphate starvation tolerance [ 190 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bHLH (basic helix-loop-helix) transcription factors constitute the second largest family in angiosperms and are universally distributed in all eukaryotic organisms [ 43 ]. The highly conserved bHLH signature domain comprises two distinct functional regions, a basic N-terminal DNA-binding region, and a helix-loop-helix region involved in protein–protein interactions via the formation of homo- and heterodimeric complexes located at the C-terminal end, which is a prerequisite for TF function [ 119 , 120 ].…”
Section: Transcription Factors Involved In Abiotic Stress Responsementioning
confidence: 99%
“…Similarly, accumulating evidence has indicated that bHLH TFs also participate in regulating various abiotic stresses. For example, the expression of AtbHLH68 , a putative non-DNA-binding bHLH gene, was altered in Arabidopsis in an organ-specific manner with exogenous application of ABA, and its overexpression conferred transgenic plants significant drought resistance, likely via regulation of ABA homeostasis [ 43 ]. Further, AtbHLH112 overexpressors displayed better ROS-scavenging abilities, as well as elevated levels of proline that led to high resistance against multiple abiotic stresses, including salt and drought [ 45 ].…”
Section: Transcription Factors Involved In Abiotic Stress Responsementioning
confidence: 99%
“…Recent studies have indicated that a number of bHLH transcription factor genes are involved in responses to abiotic stresses including drought, salt, and cold. The overexpression of AtbHLH068 and OsbHLH148 in transgenic Arabidopsis thaliana and rice, respectively, reportedly induces drought stress tolerance via abscisic acid (ABA)-and jasmonic acid (JA)-mediated signaling pathways (Seo et al, 2011;Le Hir et al, 2017). In rice, OsbHLH062, OsJAZ9, and OsNINJA form a transcriptional regulatory complex that fine-tunes the expression of JA-responsive genes involved in salt stress tolerance (e.g., OsHAK21) (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%